1991
DOI: 10.1037/0033-295x.98.2.182
|View full text |Cite
|
Sign up to set email alerts
|

A theory of if: A lexical entry, reasoning program, and pragmatic principles.

Abstract: The theory has 3 parts: (a) A lexical entry defines the information about if in semantic memory; its core comprises 2 inference schemas, Modus Ponens and a schema for Conditional Proof; the latter operates under a constraint that explains differences between (/and the material conditional of standard logic, (b) A propositional-logic reasoning program specifies a routine for reasoning from information as interpreted to a conclusion, (c) A set of pragmatic principles governs how an ;/ sentence is likely to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
221
3
12

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(241 citation statements)
references
References 74 publications
5
221
3
12
Order By: Relevance
“…Rather, in each of our recent studies (as independently confirmed by others), logic inference is associated with the activation of regions that have been linked to goal/subgoal processing in tasks requiring multiple steps and embedded operations (41) as well as coordination and selection of rules for path-finding from an initial to a final state (44,45). Such cognitive processes are intriguingly consistent with a ''rule-based'' account of deduction (59,60,61). The latter theory conceives inference as the construction of a chain of structured representations within LOT leading from premises to conclusions via intermediate transformations licensed by elementary rules of inference.…”
Section: Discussionsupporting
confidence: 57%
“…Rather, in each of our recent studies (as independently confirmed by others), logic inference is associated with the activation of regions that have been linked to goal/subgoal processing in tasks requiring multiple steps and embedded operations (41) as well as coordination and selection of rules for path-finding from an initial to a final state (44,45). Such cognitive processes are intriguingly consistent with a ''rule-based'' account of deduction (59,60,61). The latter theory conceives inference as the construction of a chain of structured representations within LOT leading from premises to conclusions via intermediate transformations licensed by elementary rules of inference.…”
Section: Discussionsupporting
confidence: 57%
“…It does not, however, reveal anything profound about reasoning proper. It does not provide evidence for or against different theories of human reasoning such as mental logic (Braine & O'Brien, 1991;Braine & Rumain, 1983;Rips, 1994), mental models (Johnson-Laird, 1983;JohnsonLaird & Byrne 1991), pragmatic schemas (Cheng & Holyoak, 1985;Cheng et al, 1986), and Darwinian algorithms (Cosmides, 1989). In the Selection Task, the various reasoning processes that have been suggested on the basis of these theories are pre-empted by processes that determine intuitions of relevance.…”
Section: Resultsmentioning
confidence: 99%
“…The rule of conditional proof, for example, allows a reasoner to assume a proposition, A, for the sake of argument, and should that assumption together with other premises lead to a conclusion, C, then the reasoner can draw a conditional conclusion, if A then C. Similarly, a conditional premise, if A then C, together with a categorical premise, A, allows a reasoner to conclude, C, which is an inference of the sort known as modus ponens. Formal theorists recognize that conditionals can be interpreted in different ways (see, e.g., Braine & O'Brien, 1991), but they have not proposed any comprehensive theory of how such interpretations arise. Rips (1994), for example, finesses this problem, taking for granted that the input to his "PSYCOP" theory is the logical form of premises.…”
Section: Alternative Theories Of Conditionalsmentioning
confidence: 99%